Creativity and marketing : the fuel for success - Pantano, Eleonora (Emerald Publishing Limited, 2021)
Creativity and Marketing: The Fuel for Success presents a diverse collection of theoretical analysis, real world evidence, and case study applications to synthesize emerging studies on how creativity is important for marketing success. Exploring themes in strategic marketing , creativity in management and communication as well as creativity in new product development, Creativity and Marketing examines a wide range of cutting-edge developments at the intersection of marketing and creative practice, including brand management, social media management, consumer behaviour, and value creation. This collection will bridge theory and practice in a fast moving and exciting field and will provide scholars of marketing, branding and consumer behaviour with lessons and strategies to implement in their own fields.
Includes index.
Keywords: Marketing.; Creative ability in business.; Business & Economics -- Marketing -- General.; Sales & marketing.; elektronické knihy; electronic books